2016
DOI: 10.1158/0008-5472.can-16-0979
|View full text |Cite
|
Sign up to set email alerts
|

RNA Sequencing Identifies Transcriptionally Viable Gene Fusions in Esophageal Adenocarcinomas

Abstract: Esophageal adenocarcinoma (EAC) is a deadly cancer with increasing incidence in the U.S., but mechanisms underlying pathogenesis are still mostly elusive. In addressing this question, we assessed gene-fusion landscapes by comprehensive RNA sequencing (RNAseq) of 55 pre-treatment EAC and 49 non-malignant biopsy tissues from patients undergoing endoscopy for Barrett’s esophagus. In this cohort, we identified 21 novel candidate EAC-associated fusions occurring in 3.33%-11.67% of EACs. Two candidate fusions were s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 14 publications
3
28
0
Order By: Relevance
“…The most prevalent fusions expected under neutral selection would be observed only 2 times, and we would expect to observe only 5 such fusions ( This analysis reveals new evidence that recurrent fusions are selected for in diverse tumors; RPS6KB1-VMP1, a fusion between the ribosomal protein kinase (Cai et al, 2015) and a vacuolar protein (VMP1) present in a 8 tumor types, is the most prevalent detected gene fusion, after TMPRSS2-ERG, across the entire TCGA cohort and supports findings by previous studies that these fusions have a driving role (Inaki et al, 2011, Blum et al, 2016; Figure 2C). Globally, 14% of the fusions (1,486) found by DEEPEST-Fusion are observed at higher rates than expected by chance (p < 1e-6); more than 11.9% of tumors (1,181) have recurrent fusions ( Figure 4 and Supplemental Table 1).…”
Section: Statistical Analysis Of Rare Fusions Shows a Selection For Fsupporting
confidence: 88%
“…The most prevalent fusions expected under neutral selection would be observed only 2 times, and we would expect to observe only 5 such fusions ( This analysis reveals new evidence that recurrent fusions are selected for in diverse tumors; RPS6KB1-VMP1, a fusion between the ribosomal protein kinase (Cai et al, 2015) and a vacuolar protein (VMP1) present in a 8 tumor types, is the most prevalent detected gene fusion, after TMPRSS2-ERG, across the entire TCGA cohort and supports findings by previous studies that these fusions have a driving role (Inaki et al, 2011, Blum et al, 2016; Figure 2C). Globally, 14% of the fusions (1,486) found by DEEPEST-Fusion are observed at higher rates than expected by chance (p < 1e-6); more than 11.9% of tumors (1,181) have recurrent fusions ( Figure 4 and Supplemental Table 1).…”
Section: Statistical Analysis Of Rare Fusions Shows a Selection For Fsupporting
confidence: 88%
“…This locus was recently shown to be recurrently amplified in lung adenocarcinoma (Campbell et al, 2016). VMP1 encodes a vacuolar membrane protein that is functionally linked to autophagy and has been found to be recurrently rearranged in several cancer types, including breast and esophageal cancer (Blum et al, 2016; Inaki et al, 2011). Interestingly, the VMP1/MIR21 locus was also the ninth most highly ranked hotspot in the indel analysis (Figure 1C), though it did not pass the FDR threshold of 0.1 ( P = 6.4 × 10 −6 ).…”
Section: Resultsmentioning
confidence: 99%
“…12,13 Although chromosomal rearrangements have been reported in EAC, no driver events caused by fusion genes have yet been described in this malignancy. Recently, Blum et al 14 identified ribosomal protein S6 kinase B1 (RPS6KB1)-vacuole membrane protein 1 (VMP1) as a fusion transcript that modulates autophagy in EAC. With the exception of this single study, however, there have been no comprehensive reports of fusion transcripts in EAC.…”
Section: Introductionmentioning
confidence: 99%